Resveratrol Protects Vascular Endothelial Cells from High Glucose–Induced Apoptosis through Inhibition of NADPH Oxidase Activation–Driven Oxidative Stress. (3rd June 2013) - Chen, Feng; Qian, Li‐Hua; Deng, Bo; Liu, Zhi‐Min; Zhao, Ying; Le, Ying‐Ying
Summary Introduction Hyperglycemia‐induced oxidative stress has been implicated in diabetic vascular complications in which NADPH oxidase is a major source of reactive oxygen species (ROS) generation. Resveratrol is a naturally occurring polyphenol, which has vasoprotective effects in diabetic animal models and inhibits high glucose (HG)–induced oxidative stress in endothelial cells. Aims We aimed to examine whether HG‐induced NADPH oxidase activation and ROS production contribute to glucotoxicity to endothelial cells and the effect of resveratrol on glucotoxicity. Results Using a murine brain microvascular endothelial cell line bEnd3, we found that NADPH oxidase inhibitor (apocynin) and resveratrol both inhibited HG‐induced endothelial cell apoptosis. HG‐induced elevation of NADPH oxidase activity and production of ROS were inhibited by apocynin, suggesting that HG induces endothelial cell apoptosis through NADPH oxidase–mediated ROS production. Mechanistic studies revealed that HG upregulated NADPH oxidase subunit Nox1 but not Nox2, Nox4, and p22phox expression through NF‐κB activation, which resulted in elevation of NADPH oxidase activity and consequent ROS production. Resveratrol prevented HG‐induced endothelial cell apoptosis through inhibiting HG‐induced NF‐κB activation, NADPH oxidase activity elevation, and ROS production. Conclusions HG induces endothelial cell apoptosis through NF‐κB/NADPH oxidase/ROS pathway, which was inhibited by resveratrol. Our findings provide new potential therapeutic targets against brain vascular complications of diabetes.